Development of a method to clinically identify the position of the lingual nerve relative to the third molar region - Sanaa Aljamani; Callum Youngson; Fadi Jarad; Francis O'Neill (Translational Research in Anatomy, 2020)
Objectives: To develop a method to clinically identify the position of the lingual nerve within the lingual tissue in the third molar region by electro-stimulation. Methods: Following ethical committee approval a cross-sectional study was performed in 20 healthy participants. A proprietary Electric Pulp Tester (EPT) was used intra-orally to stimulate the lingual nerve and, to identify the vertical position of the lingual nerve, measurements were taken when subjects felt a projected tingling sensation in the tongue as the stimulation probe was placed directly over the nerve. The nerve location was investigated in three positions in relation to the third molar: Point A at the retromolar pad; Point C at the distolingual attached gingivae of the erupted lower second molar and; Point B at the midline of the erupted third molar (or when the third molar was unerupted, midway between Points A & C). Results: Out of 20 participants 18 (90%) were able to identify the projected tingling sensation on the tongue upon stimulating the nerve, allowing the nerve position to be identified. The mean vertical height of the lingual nerve relative to the third molar was 10.5, 10.75 and 12.5 mm for positions A, B and C respectively. The sensation related to nerve stimulation was well accepted by participants with minimal adverse events. Conclusion: We have demonstrated that stimulation of the lingual nerve with an EPT can clinically identify the position of the lingual nerve in situ. This technique may be useful for the clinical determination of lingual nerve position prior to third molar surgery. Keywords: Lingual nerve, Electric pulp tester, Anatomy, Extraction, Mapping